The measurement of the effectiveness of positive parenting education and social and emotional learning education for parents of preschool children on their children's adaptive behavior - Fallah, Shirin; Abolmaali Alhosseini, Khadijeh; Sabet, Mehrdad (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to determine the effectiveness of positive parenting education and the social and emotional learning education of parents of preschool children on their children's adaptive behavior. Methods: The method of this study is quasi-experimental with a three-group pretest-posttest design of two study groups and a control group and a one-month follow-up. The statistical population of the study consisted of parents of preschool children with their children in Tehran in 2019. Accordingly, 45 mothers were selected by convenience sampling method and randomly divided into two study groups (15 people in each group) and one control group (15 people). One of the study groups received the Saunders Positive Parenting Education, 2005, and the other study group received the Kessel Social-Emotional Learning Education, 2003, for eight 90-minute sessions, and the control group was on the waiting list. The research tool included the Vineland Adaptive Behavior Scale (1965), which was assessed in three stages of pre-test, post-test, and follow-up. The repeated measures variance method was used to analyze the data. Results: The results indicated that the positive parenting intervention and socio-emotional learning are effective on individual independence (F = 18.19 and P = 0.001), social behavior (F = 4.69 and P = 0.010) and total score of adaptive marital behavior (F = 15.39 and P = 0.001). This result was stable at the follow-up stage. Conclusion: The findings revealed that both interventions employed in this study can significantly improve adaptive behavior in children. Therefore, these educational services can be used in preschool centers to improve adaptive behavior among children.